Phospholipids containing polyunsaturated fatty acyl groups are mitogenic for normal mouse mammary epithelial cells in serum-free primary cell culture. - Imagawa, W (1989)
Epithelial cells obtained by collagenase digestion of mammary glands from virgin BALB/c mice were cultured in collagen gels in serum-free basal medium containing insulin (10 micrograms/ml), to which lipids or growth factors were added. Synthetic phospholipids were added as liposomes. Dilinoleoyl phosphatidic acid or phosphatidylserine or epidermal growth factor stimulated multifold growth. The optimum mitogenic effect of the phospholipids was dependent upon the presence of a polyunsaturated fatty acid esterified to the sn-2 position of the glycerol moiety. Dilinoleoyl phosphatidylcholine also stimulated growth but was generally less stimulatory than phosphatidylserine or phosphatidic acid, and phosphatidylethanolamine did not stimulate growth. Studies using phospholipids radiolabeled in either the sn-2 fatty acyl group or the glycerol backbone showed that the relative effect of phospholipids on growth did not correlate directly with the extent of their incorporation into cellular lipid, indicating that phospholipid turnover was the more important determinant for mitogenesis. Analysis of phosphatidic acid-stimulated growth suggested that both cAMP-dependent and cAMP-independent pathways were involved. Thus, mitogenic phospholipids stimulate proliferation by activating (directly or indirectly) multiple growth-regulatory pathways in mammary epithelial cells.